Estudio de las cepas de estreptococos del grupo mutans presentes en binomios madre-hijo (2010)
ABSTRACT: Mutans Streptococci (MS) are a group of bacteria associated with the pathogenesis of dental caries. Evidence indicates that direct mother-to-infant contact during the eruption of the first primary tooth is a common mode of MS transmission, but this could also happen in pre dentate children, making possible an elevated dental caries risk. The objective was to assess the presence of MS in the pre-dentate infant and his or her mother, and to compare the strains using chromosomal DNA fingerprinting to ascertain the importance of vertical transmission before dental eruption. Methods: sixty pre-dentate infant-mother pairs were examined for the presence of MS using a Mitis Salivarius Agar. The strains harvested from the pre-dentate infants and their mothers (positive pairs) were analyzed by chromosomal DNA fingerprinting. Results: from the initial group of 60 pre-dentate infant-mother pairs, 12 were positive pairs. Genomic fingerprints of MS strains harvested from the 12 positive pairs were examined, and a total of 172 strains were found. Whole genomic DNA was purified and digested with HaeIII, fragments were separated by agarose gel electrophoresis. Genomic fingerprints were compared by the Quantity One Program. Homology in at least one strain was observed among 9 pre dentate infant–mother pairs. Conclusion: results support the notion of vertical transmission of MS, and confirm their presence in the pre dentate stage.